Evaluasi Penyelenggaraan Pendaftaran Pasien di Klinik X Kabupaten Malang - Nita Dwi Nur Aini; Wisoedhanie Widi Anugrahanti (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
Clinics are one of the health service facilities that are much sought after and needed to support health improvement both individually and in society. Clinics must improve the quality of their services, one of which is the patient registration system which is the leading service unit for every health service facility. Patient registration services must be able to include important information about patient social data as the basis for creating a health information system. The aim of this research is to evaluate the implementation of medical records in the registration section at the Modern Poncokusumo Clinic, Malang Regency. This research method uses qualitative descriptive research with a total of 4 respondents. Data collection was carried out by interviews and observations and presented in narrative form. The research results explain that there are several things in the implementation of patient registration that are not appropriate, namely human resources, infrastructure and procedures, causing the medical record registration activity (process) to be not optimal. The results (output) of the activity include efforts to improve the patient registration system so that it can run quickly, completely, effectively and efficiently.